Análise da literatura brasileira de siderurgia - Gusmão, Heloisa Rios (1977)
Bibliotric analysis of the literature on Iron and Steel published in "Siderurgia Brasileira 1960/72" focusing on serials and authors 826 articles from 42 serials and 726 authors were analysis amouting to 1.2 article/author. The analysis proved the existence of representative nucleus of serials and a low productivity of authors despite of the length of the period of literature analysed.